Handbook of visual communication theory, methods, and media - Josephson, Sheree; Kelly, James D. 1957-; Smith, Ken 1947 August 14- (Routledge communication series)
"This Handbook of Visual Communication explores the key theoretical areas and research methods of visual communication. With chapters contributed by many of the best-known and respected scholars in visual communication, this volume brings together significant and influential work in the discipline"--Provided by publisher.